ASPECTS ON THE IMPLEMENTATION OF PSYCHOLOGICAL RESOURCES IN SWIMMING AT AN EARLY AGE THROUGH SURVEYS - Burac Daniela Giconda; Furdu Dragoş (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The use of the survey, as a special category of investigation, on a specific professional category very well defined in the specialty of the activity, is extremely beneficial to improve the efficiency of swimming training at early age. Children's psychological resources, which some teachers marginalize, out of ignorance or out of pragmatism, can be very important in the teaching - learning process, the outcomes of children who are encouraged to reveal and develop their skills and abilities through these resources are spectacular. Therefore the survey reveals the concern of swimming trainers to train children in early childhood and to transform the extrinsic motivations into intrinsic ones, with obviously superior results at the level of assimilation of knowledge and skills by the children.